2010
DOI: 10.1891/0889-8391.24.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy in the Treatment and Management of Sex Offenders

Abstract: In this article, current methods of conceptualizing and treating adult sexual offending are reviewed. First, the Risk-Needs-Responsivity (RNR) approach to sex offender management is presented and critiqued. Then, the newer Good Lives Model is discussed and contrasted with the aforementioned RNR approach. The discussion of these approaches to sex offender management and rehabilitation is followed by a review of those cognitive-behavioral therapy (CBT) techniques used to treat risk factors associated with sex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…Needless to say, multicultural research is also necessary in treatment programming. One of the state-of-the-art ways that we manage those who commit sexual offenses is through the RNR approach, which stipulates that management should match the offender’s cultural background (Andrews & Bonta, 1998; Schaffer, Jeglic, Moster, & Wnuk, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, multicultural research is also necessary in treatment programming. One of the state-of-the-art ways that we manage those who commit sexual offenses is through the RNR approach, which stipulates that management should match the offender’s cultural background (Andrews & Bonta, 1998; Schaffer, Jeglic, Moster, & Wnuk, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the increased number of programs in existence and their similarity in content, there continues to be inconsistent findings reported from studies on their effectiveness (Abracen, Looman, Ferguson, Harkins, & Mailloux, 2011; Duwe & Goldman, 2009; Schaffer, Jeglic, Moster, & Wnuk, 2010; Woodrow & Bright, 2011). Early evaluations of such programs reported that the treatment programs were either ineffective or the results were inconclusive due to methodological issues with the available studies (Furby, Weinrott, & Blackshaw, 1989; Quinsey, Harris, Rice, & Lalumiere, 1993).…”
mentioning
confidence: 99%
“…In particular, CBT outside of criminal justice is used to address phobias, anxiety, and depressive thoughts (Padesky & Beck, 2003 ) whilst within the CJS it addresses cognitive distortions that support offending behaviour. For example, CBT is used widely with people convicted of sexual offences and may address belief systems that relate to offence‐related beliefs (e.g., that a victim desires sex), or minimisation of personal responsibility (Schaffer et al, 2010 ). There is, therefore, an inferential leap to assume that a treatment that addresses depressive thoughts can address criminogenic thoughts.…”
Section: Introductionmentioning
confidence: 99%